2010
DOI: 10.1177/112067211002000115
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Phacoemulsification with Pars Plana Vitrectomy for Management of Posteriorly Dislocated Nucleus or Lens Fragments

Abstract: Immediate vitrectomy and intravitreal phacoemulsification is a surgical option in the management of posteriorly dislocated nucleus/lens fragments without much risk of retinal damage. It is relatively safe and most patients achieved a good visual outcome. The risk of postoperative complications including uveitis, secondary glaucoma, and cystoid macular edema could be minimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In vitro study showed that PFCL is directly toxic to human retinal pigment epithelial cells when exposed to the cells for 7 days 21. Ruiz–Moreno et al 22 and Soliman Mahdy et al 23 have performed intravitreal phacoemulsification with a conventional probe devoid of its silicone sleeve for removal of dislocated nucleus/lens fragments. Complications reported in their series were retinal tears at the time of surgery and retinal detachment postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro study showed that PFCL is directly toxic to human retinal pigment epithelial cells when exposed to the cells for 7 days 21. Ruiz–Moreno et al 22 and Soliman Mahdy et al 23 have performed intravitreal phacoemulsification with a conventional probe devoid of its silicone sleeve for removal of dislocated nucleus/lens fragments. Complications reported in their series were retinal tears at the time of surgery and retinal detachment postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Although our PPV with the phacoemulsification method in the vitreous cavity17,18 does not require any enlargement of the scleral limbal wound, it is possible that a retinal tear or vitreous hemorrhage could occur due to the ultrasound energy present 19. Other reported methods that can be used in such cases involve lifting the lens into the anterior chamber, with removal then performed via a scleral limbal wound 5,10.…”
Section: Discussionmentioning
confidence: 99%
“…30,31,36,[47][48][49][50][51] However, some studies suggest that vitrectomy undertaken at the time of cataract surgery (if a vitreoretinal surgeon is available) or within 3 weeks, may improve overall visual outcome and reduce the risk for chronic elevation of intraocular pressure. [52][53][54] One systematic review and meta-analysis of retrospective interventional case series found optimal timing for vitrectomy in cases not requiring early PPV (i.e., in cases involving retinal detachment or endophthalmitis) to be between days 3 to 7 following cataract surgery. 55 A significant association between retinal detachment and PPV performed more than 30 days after cataract surgery has also been shown.…”
Section: Timing Of Pars Plana Vitrectomymentioning
confidence: 99%